2008
DOI: 10.1016/j.cub.2008.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenic Capacity of Endogenous G4 DNA Underlies Genome Instability in FANCJ-Defective C. elegans

Abstract: To safeguard genetic integrity, cells have evolved an accurate but not failsafe mechanism of DNA replication. Not all DNA sequences tolerate DNA replication equally well [1]. Also, genomic regions that impose structural barriers to the DNA replication fork are a potential source of genetic instability [2, 3]. Here, we demonstrate that G4 DNA-a sequence motif that folds into quadruplex structures in vitro [4, 5]-is highly mutagenic in vivo and is removed from genomes that lack dog-1, the C. elegans ortholog of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

13
192
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 194 publications
(208 citation statements)
references
References 26 publications
13
192
1
2
Order By: Relevance
“…With its 22-kb open reading frame (ORF) and a clearly recognizable mutant phenotype, the unc-22 locus provides an endogenous mutational sink that is largely non-discriminatory to size: all alterations that change the reading frame (whether one bp or tens of kb) will render worms insensitive to the muscle hypercontracting effect of the cholinergic agonist levamisole 21 . Earlier work revealed that sequences that match the G4 DNA consensus G 3-5 N 1-3 G 3-5 N 1-3 G 3-5 N 1-3 G 3-5 induce deletions in dog-1-deficient animals; equienergetic G-rich DNA sequences that do not match this motif (for example, G3C DNA or CG repeats) are perfectly stable 17 . However, because of the relatively high, size-related, background level of spontaneous mutagenesis in unc-22 (B10 À 6 ), we chose to target only those G4 sequences that we previously found to have high mutagenic potential (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…With its 22-kb open reading frame (ORF) and a clearly recognizable mutant phenotype, the unc-22 locus provides an endogenous mutational sink that is largely non-discriminatory to size: all alterations that change the reading frame (whether one bp or tens of kb) will render worms insensitive to the muscle hypercontracting effect of the cholinergic agonist levamisole 21 . Earlier work revealed that sequences that match the G4 DNA consensus G 3-5 N 1-3 G 3-5 N 1-3 G 3-5 N 1-3 G 3-5 induce deletions in dog-1-deficient animals; equienergetic G-rich DNA sequences that do not match this motif (for example, G3C DNA or CG repeats) are perfectly stable 17 . However, because of the relatively high, size-related, background level of spontaneous mutagenesis in unc-22 (B10 À 6 ), we chose to target only those G4 sequences that we previously found to have high mutagenic potential (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1a). As of the low mutagenic capacity of minimal G4 motifs 17 , we obtained qua739 deletions at its original genomic location using a PCR-based approach (see Methods section). Indeed, deletions triggered by this motif have a very sharply positioned 3 0 junction, with none mapping within the motif (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations